TANGGUNG JAWAB HUKUM PELAKU USAHA TERHADAP KONSUMEN ATAS PENJUALAN OBAT DENGAN HARGA ECERAN TERTINGGI PADA APOTEK - A.A. Dody Hartawan (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
In everyday life, the buying and selling transaction process will continue to take place, which will be carried out by business actors and consumers. A standard or price limit set on the selling price of a drug will provide a guarantee to consumers in terms of purchasing drugs at the price set by the Company which will then be sold by the business actor to consumers. The price set is in the form of (HET) Highest Retail Price) which has been set by the Company and has received price approval from the government through the relevant agency. In this case, the formulation of the problem to be discussed is. What is the form of legal protection for consumers who purchase drugs above the Highest Retail Price (HET) and What is the responsibility of business actors towards consumers who are harmed in purchasing drugs above the Highest Retail Price (HET). The type of research used in this study is a normative research type. A form of legal protection that can be put forward for consumers who purchase drugs above the highest retail price is in the form of preventive and repressive legal protection and the responsibility imposed on business actors can be in the form of criminal sanctions, fines, and administrative sanctions.